An Analysis on William Ernest Henley’s Invictus - Malinda, Ayu (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
The research is an analysis the poem structure of William Ernest Henley Invictus. The purpose of this research is to understand the structure that used in thepoem of William Ernest Henley Invictus. The data were taken fromdocumentation of Invictus poem and biographical of the poet. Theresearcher used objective approach as data analysis method. The structureof poetry is consisting of two structures, namely; physical structure and innerstructure. The physical structure is consisting of six sections, they are diction,imagery, concrete word, figurative language, version and typography. While, the inner structure is divide on four proportion they are theme, tone, feelingand mandate. To make a good poetry the poet should pay attention in theelements of poetry, especially the structure of poetry.